Endoplasmic reticulum and autophagy in rat hepatocytes. - Novikoff, A B (1978)
Electron microscopy of hepatocytes in both normal rat liver and rat liver treated to induce hyperplasia of smooth endoplasmic reticulum shows that autophagic vacuoles and residual bodies (types of lysosomes) are continuous with endoplasmic reticulum.